Analysis of The Impact of Fisheries on Marine Ecology - Liu, Zezhen; Xiong, Ziliang; Yu, Haochen (Transactions on Environment, Energy and Earth Sciences, 2024)
The marine ecosystem is now a noticeable topic in the worldwide range, affecting the lives of billions of people as well as the entire environment of the planet. The fishing industry, which is closely combined with the marine ecosystem, might have a wide negative impact on the marine ecosystem, such as the destruction of marine biodiversity, destruction of biological habitats, biological invasions, and seawater pollution. The purpose of this paper is to conduct a clear study on the structure of fisheries and to find out the exact negative impacts of fisheries on the marine environment in order to discuss the need to protect the marine ecosystem and resources. Based on the results of this paper, it is clear that there are various need of fishing industry, including seafood fishing, seafood processing, seafood circulation, and aquaculture. And it could have a negative influence on marine ecosystems through the destruction of marine habitats, biological invasion as well as water pollution. Therefore, human beings should conserve marine biodiversity and protect the marine environment by reducing the use of plastic products, garbage sorting, recycling and treatment of discharged wastewater. These methods are eco-friendly and conducive to maintaining the balance of the ecosystem and the sustainable development of the economy in the future.